A review of computational methods for studying oscillating water columns – the Navier-Stokes based equation approach. (March 2023) - Opoku, F.; Uddin, M.N.; Atkinson, M.
Abstract: This review evaluates the state-of-the-practice numerical tools used to predict the performance of Oscillating Water Column (OWC). The OWC is a widely studied Wave Energy Converter that provides a reliable form of renewable form of electricity that can potentially meet global energy needs. However, the fluid-flow phenomena affecting its hydrodynamic performance are not fully understood. While there has been the successful full-scale deployment of OWCs, various computational methods are being explored to optimize this technology. Potential flow theory is commonly used to evaluate the efficiency of OWCs; however, this assumption tends to over-predict the hydrodynamic performance. Recently, numerical studies using a diverse set of commercial, open-source, or in-house Computational Fluid Dynamics (CFD) using Reynolds Averaged Navier Stokes (RANS) and Large-Eddy Simulation codes show a better comparison to available experimental results but are computationally expensive. ANSYS Fluent was found to be the most widely used CFD code applied to the study of the OWCs, with a high degree of accuracy in terms of experimental validation of numerical results. Highlights: A detailed review of CFD methodologies for the OWC is presented. For inviscid flow, few articles applied CFD compared to Potential Flow theories. Most viscous flow simulations of the OWC assume full turbulence. The standard k-ε model was the most widely used RANS model. ANSYS Fluent was the most widely used CFD code used to study OWC.